Housing system and urbanization in the People's Republic of China - Jie Chen (Asian Development Bank Institute (ADBI), 2016)
This paper examines how transformations in the housing system in the People's Republic of China (PRC) influence the PRC pattern of urbanization. It first discusses how housing policies determine the supply and demand of housing in urban PRC and subsequently analyzes how the changes in the mode of housing provision have affected rural-urban migration, intercity labor mobility, the financing of urban infrastructure, and general urban economic activities in the PRC. The PRC experience of the interaction between the housing system and urbanization is unique, but it clearly indicates that an effective housing system that can responsively provide adequate and affordable housing is crucial to the success of inclusive and equitable urbanization.
Keywords: R30; R38; 330; housing policy; rural-urban migration; intercity labor mobility; urban infrastructure; urbanization; inclusive urbanization; equitable urbanization